Robot-assisted partial nephrectomy in contemporary practice - Tanagho, Youssef S.; Bhayani, Sam B.; Figenshau, Robert S. (Frontiers in Oncology, 2013)
Laparoscopic renal surgery is associated with reduced blood loss, shorter hospital stay, enhanced cosmesis, and more rapid convalescence relative to open renal surgery. Laparoscopic partial nephrectomy is a minimally invasive, nephron-sparing alternative to laparoscopic radical nephrectomy for the management of small renal masses. While offering similar oncological outcomes to laparoscopic radical nephrectomy, the technical challenges and prolonged learning curve associated with laparoscopic partial nephrectomy limit its wider dissemination. Robot-assisted partial nephrectomy, although still an evolving procedure with no long-term data, has emerged as a viable alternative to laparoscopic partial nephrectomy, with favorable preliminary outcomes. This article provides an overview of the role of robot-assisted partial nephrectomy in the management of renal cell carcinoma. The clinical indications and principles of surgical technique for this procedure are discussed. The oncological, renal functional, and perioperative outcomes of robot-assisted partial nephrectomy are also evaluated, as are complication rates.